Individual and Technological Factors Influencing Islamic Investment Decisions: A Maqāṣid al-Sharī‘ah Perspective - S. Br Sembiring, Suci Ramadhana; Soemitra, Andri; Nasution, Juliana (UIN Siber Syekh Nurjati Cirebon, 2025)
The Islamic capital market is increasingly gaining attention as an investment alternative that aligns with Islamic principles. However, student participation in this market remains relatively low. This study aims to examine the influence of pocket money, technological innovation, and risk perception on investment decisions in the Islamic capital market. Employing a quantitative approach with a survey method, data were collected from 100 students at UIN North Sumatra through an online questionnaire distributed via Google Forms. The data were analyzed using Partial Least Squares (PLS) with the assistance of SmartPLS software. The results reveal that technological innovation has a positive and significant effect on investment decisions, indicating that advanced digital investment platforms, online education, and accessible information play a crucial role in encouraging student participation. In contrast, pocket money and risk perception do not exhibit significant influence, although both show moderate contributions. These findings suggest that enhancing technological access and digital literacy may be more effective in fostering Islamic investment behavior among students than focusing solely on financial capacity or risk attitudes. This study reflects how Islamic investment behavior among students supports the realization of Maqāṣid al-Sharī‘ah, particularly in preserving wealth (ḥifẓ al-māl) and intellect (ḥifẓ al-‘aql).Keywords: Islamic Investment; Individual Factors; Technological Innovation; Risk Perception; Maqāṣid al-Sharī‘ah